Highlights and outcome of MACS G20 countries meet at Varanasi - Malhotra, S K; Mandal, Bikas; Prakash, Ravi (Indian Farming, 2023)
The G20-Meeting of Agricultural Chief Scientists (MACS) is a unique platform to discuss knowledge, science and technologies based solutions for food and nutrition security and strengthening cooperation among the member nations. The ICAR-DARE was assignedresponsibility to take lead in organization of 12th Meeting of Agricultural Chief Scientists (MACS) at Varanasi from 17–19th April 2023, with theme of Sustainable Agriculture and Food Systems for Healthy People and Planet. About 80 delegates from G20 Member States participated to discuss various issues of agriculture research and development including food security and nutrition, climate smart agriculture, digital agriculture and public private partnership. The Millets and Other Ancient Grains International Research Initiative (MAHARISHI) was proposed from India for deliberations as G20 initiative.